Mediational Model of Multiple Sclerosis Impairments, Family Needs, and Caregiver Mental Health in Guadalajara, Mexico - Melody N. Mickens; Paul B. Perrin; Adriana Aguayo; Brenda Rabago; Miguel A. Macías-Islas; Juan Carlos Arango-Lasprilla (Behavioural Neurology)
Individuals with multiple sclerosis (MS), especially those living in Latin America, often require assistance from family caregivers throughout the duration of the disease. Previous research suggests that family caregivers may experience positive and negative outcomes from providing care to individuals with MS, but few studies have examined the unmet needs of individuals providing care to family members with MS and how these unmet needs may mediate the relationship between MS symptoms and caregiver mental health. The current study examined the relationships among MS impairments (functional, neurological, cognitive, behavioral, and emotional), unmet family needs (household, informational, financial, social support, and health), and caregiver mental health (satisfaction with life, anxiety, burden, and depression) in a sample of 81 MS caregivers from Guadalajara, Mexico. A structural equation model demonstrated the mediational effect of unmet family needs on the relationship between MS impairments and caregiver mental health. These findings suggest that intervention research on MS caregivers in Latin America may consider focusing on caregiver mental health problems by addressing unmet family needs and teaching caregivers ways to manage the impairments of the individual with MS.